Core self-evaluations and perceived classmate support: Independent predictors of psychological adjustment - Yudes Gómez, Carolina; Chamizo-Nieto, María Teresa; Peláez-Fernández, María Ángeles; Extremera-Pacheco, Natalio (Wiley, 2024)
Introduction The main aim of this research was to explore the contribution of both core self-evaluations (CSE) and classmate support as unique predictors of positive and negative psychological adjustment among adolescents. Methods In a cross-sectional study, 2,293 Spanish adolescents (Mage = 14.07) completed the Core Self-Evaluations Scale, the Classmate Support subscale, the Satisfaction with Life Scale, the Depression, Anxiety, and Stress Scales and the Frequency of Suicidal Ideation Inventory. Pearson correlations among assessed variables were examined, and three hierarchical regression analyses were conducted to examine the predictive role of CSE and classmate support on life satisfaction, depressive symptomatology, and suicidal ideation. Results Both CSE and classmate support were positively related to life satisfaction and negatively related to depressive symptoms and suicidal ideation. Hierarchical regression analyses identified CSE and classmate support as independent predictors of both positive and negative psychological outcomes in this sample. These results indicated support for a comprehensive model involving CSE and classmate support as additive predictors of both positive and negative outcomes among adolescents. Conclusion These findings underscore the unique and additive role of both individual (i.e., CSE) and, to a lower degree, social factors (i.e., classmate support) to augment the prediction model of positive and negative psychological adjustment among adolescents. Practical implications are discussed, focusing on preventive programs that include strategies to increase positive self-appraisals and create a supportive classroom climate.
Keywords: Adolescentes - Psicología; Adolescentes - Trastornos de la conducta; Salud mental; Psicología de la educación; Psicología social; Core self-evaluations; Life satisfaction; Perceived classmate support; Depression; Suicidal ideation